District-based Rental Value Coefficients for Shopping Mall Development in Istanbul - Fatma Bengü Yoğurtçu; Almula Köksal (Journal of Contemporary Urban Affairs, 2024)
This study investigates the district-based rental value coefficients for shopping malls in Istanbul, a city with significant commercial real estate activities. The research focuses on identifying regional and district variations in rental income values, crucial for urban retail investment success. Data were collected from 101 active shopping malls across 39 districts and analyzed using arithmetic mean and proportional rate methods. The findings indicate that districts such as Bakırköy, Beşiktaş, and Kadıköy have the highest rental values, while Esenyurt, Arnavutköy, Sultanbeyli, and Sancaktepe rank lowest. These insights provide valuable guidance for investors during the feasibility phase of shopping mall projects, highlighting the importance of location in achieving financial success. The study emphasizes the role of socio-economic conditions and accessibility in rental value determination, offering a detailed analysis that contributes to the socio-economic dimension of urban studies. The results guide retail investors in utilizing district-based coefficients for more accurate feasibility assessments, ultimately supporting sustainable commercial real estate development and urban improvement.